Metastatic intraocular chondrosarcoma in a dog - Rodrigues, Emilio F. [UNESP]; Ribeiro, Alexandre P. [UNESP]; Perlmann, Eduardo; Brooks, Dennis E.; Laus, Jose Luiz [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Chondrosarcoma accounts for about 10% of all canine bone tumors and is the second most common primary bone tumor in dogs. In veterinary medicine, chondrosarcomas are classified as skeletal and extraskeletal. Extraskeletal chondrosarcomas are mesenchymal neoplasms of soft tissues and visceral organs that produce neoplastic chondrocytes in a fibrillary matrix. There is no involvement of bone or periosteal tissues in extraskeletal chondrosarcomas. The aim of this report is to describe the first case of a metastatic intraocular extraskeletal chondrosarcoma in a dog.
Keywords: chondrosarcoma; Dog; Eye; uvea